Anode-free all-solid-state battery

By adopting anode -free design and porous layer structures in full solid batteries, combined with the use of seed crystal materials, the energy density and life of the full solid battery are solved, and the battery performance of high energy density and long life is achieved.

CN112928277BActive Publication Date: 2025-01-28HYUNDAI MOTOR CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202010431990.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-06
Filing Date
2020-05-20
Publication Date
2025-01-28
Estimated Expiration
2040-05-20

AI Technical Summary

Technical Problem

The energy density and power output performance of all-solid state batteries are lower than that of conventional lithium-ion batteries using liquid electrolytes, and the anode active materials such as graphite have volume expansion and contraction during charging and discharging, resulting in a shorter battery life.

Method used

Using anode -free solid battery design, including anode collector layer, porous layer, solid electrolyte layer and composite cathode layer, the porous layer has a three -dimensional connection frame and high porosity, and the seed crystal material is set on the interface Storage and conversion efficiency.

Benefits of technology

It significantly improves the energy density of the weight and volume of the all -solid -state battery, prolongs the battery life, and avoids short -circuit problems caused by anode volume expansion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112928277B_ABST
    Figure CN112928277B_ABST
Patent Text Reader

Abstract

The present disclosure relates to an anode-free all-solid-state battery, which includes a porous layer capable of occluding and releasing lithium without a typical composite anode having an anode active material, thereby greatly improving the energy density of the all-solid-state battery. The all-solid-state battery includes: an anode collector layer; a porous layer, which is disposed on at least one surface of the anode collector layer and is configured to include a three-dimensional interconnected framework to form pores in the porous layer; a solid electrolyte layer, which is disposed on the porous layer; and a composite cathode layer, which is disposed on the solid electrolyte layer, wherein a seed material is disposed at the interface between the anode collector layer and the porous layer and at the interface between the porous layer and the solid electrolyte layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an anode-less all-solid-state battery, and more particularly, to an all-solid-state battery that includes a porous layer capable of occluding and releasing lithium without including a typical composite anode having an anode active material, thereby greatly improving the energy density of the all-solid-state battery. Background Art

[0002] Secondary batteries that can be charged and discharged are used not only in small electronic devices such as mobile phones, notebook computers, etc., but also in large transportation vehicles such as hybrid vehicles, electric vehicles, etc. Therefore, it is necessary to develop secondary batteries with higher stability and energy density.

[0003] Conventional secondary batteries are generally configured to form a single cell using an organic solvent (organic liquid electrolyte), and thus the secondary battery has limitations in improving stability and energy density.

[0004] Meanwhile, all-solid-state batteries using inorganic solid electrolytes have recently attracted much attention because they are based on technology that does not include organic solvents and can therefore manufacture safer and simpler single cells.

[0005] However, the energy density and power output performance of all-solid-state batteries cannot match those of conventional lithium-ion batteries using liquid electrolytes. In order to solve the above problems, intensive research is being conducted on improving the electrodes of all-solid-state batteries.

[0006] In particular, the anode of the all-solid-state battery is mainly formed of graphite. In this case, ion conductivity can only be ensured when an excess of a solid electrolyte with a large specific gravity is added together with graphite, so the energy density per unit weight is very low compared to lithium-ion batteries. Moreover, when lithium metal is used as the anode, there are technical limitations in terms of price competitiveness and large-area realization. Summary of the invention

[0007] Therefore, an object of the present disclosure is to provide an all-solid-state battery whose energy density per unit weight and energy density per unit volume are greatly improved.

[0008] The object of the present disclosure is not limited to the above contents, and the object of the present disclosure will be clearly understood through the following description, and can be achieved by the means described in the claims and their combination.

[0009] An embodiment of the present disclosure provides an all-solid-state battery, which includes: an anode current collector layer; a porous layer, which is arranged on at least one surface of the anode current collector layer and is configured to include a three-dimensional interconnected framework to form pores in the porous layer; a solid electrolyte layer, which is arranged on the porous layer; and a composite cathode layer, which is arranged on the solid electrolyte layer, wherein seed material is arranged at the interface between the anode current collector layer and the porous layer and at the interface between the porous layer and the solid electrolyte layer.

[0010] The anode current collector layer may include a metal selected from the group consisting of copper, nickel, and combinations thereof.

[0011] The anode current collector layer may have a porosity of less than 1%, or a thickness of 1 μm to 20 μm.

[0012] The frame may include a metal selected from the group consisting of copper, nickel, and combinations thereof.

[0013] The porous layer may have a thickness of 1 μm to 100 μm, or a porosity of 10% to 99%.

[0014] The porous layer may further include at least one selected from an ionic liquid, a binder, and a solid electrolyte filled in the pores.

[0015] The porous layer may have a multi-layer structure.

[0016] The porous layer having a multi-layer structure may be configured such that the size of pores of the layer in contact with the anode current collector layer is larger than the size of pores of the layer in contact with the solid electrolyte layer.

[0017] A seed material may be provided at the interface between the layers of the porous layer.

[0018] The composite cathode layer may include a cathode active material layer disposed on the solid electrolyte layer and a cathode current collector layer disposed on the cathode active material layer.

[0019] The seed material may be selected from the group consisting of lithium (Li), indium (In), gold (Au), bismuth (Bi), zinc (Zn), aluminum (Al), iron (Fe), tin (Sn), titanium (Ti), and combinations thereof.

[0020] The seed material may be deposited or coated on at least one surface of at least one of the anode current collector layer and the porous layer.

[0021] The seed material may be arranged to not completely cover the interface.

[0022] The seed material may be uniformly distributed at the interface and occupy 1% to 50% of the area of ​​the interface.

[0023] The all-solid-state battery may include a three-electrode unit cell configured such that a composite cathode layer, a solid electrolyte layer, a porous layer, an anode current collector layer, a porous layer, a solid electrolyte layer, and a composite cathode layer are sequentially stacked.

[0024] According to the present disclosure, the energy density per unit weight of an all-solid-state battery and the energy density per unit volume of an all-solid-state battery can be greatly improved.

[0025] According to the present disclosure, the all-solid-state battery does not include an anode active material such as graphite, and thus the anode does not have volume expansion during charge and discharge, so the life of the all-solid-state battery can be significantly increased.

[0026] The effects of the present disclosure are not limited to the above, and should be understood to include all effects that can be reasonably expected from the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1A An all-solid-state battery according to a first embodiment of the present disclosure is shown;

[0028] Figure 1B yes Figure 1A An enlarged view of area A;

[0029] Figure 1C yes Figure 1A an enlarged view of region B;

[0030] Figure 2 Schematic diagram of a porous layer of an all-solid-state battery;

[0031] Figure 3A An all-solid-state battery according to a modification of the first embodiment of the present disclosure is shown;

[0032] Figure 3B yes Figure 3A An enlarged view of region C;

[0033] Figure 4 is a top view showing an anode current collector layer and a seed material formed on a surface of the anode current collector layer according to the present disclosure;

[0034] Figure 5 An all-solid-state battery according to a second embodiment of the present disclosure is shown; and

[0035] Figure 6 An all-solid-state battery according to a modification of the second embodiment of the present disclosure is shown. DETAILED DESCRIPTION

[0036] According to the following preferred embodiments in conjunction with the accompanying drawings, the above and other purposes, features and advantages of the present disclosure will be more clearly understood. However, the present disclosure is not limited to the embodiments disclosed herein and can be modified into different forms. These embodiments are provided to fully explain the present disclosure and fully convey the spirit of the present disclosure to those skilled in the art.

[0037] In all the accompanying drawings, the same reference numerals refer to the same or similar elements. For the sake of clarity of the present disclosure, the size of the structure is depicted as being larger than its actual size. It will be understood that, although terms such as "first", "second" and the like can be used to describe various elements in this article, these elements are not limited by these terms. These terms are only used to distinguish one element from another element. For example, without departing from the scope of the present disclosure, the "first" element described below can be referred to as the "second" element. Similarly, the "second" element can also be referred to as the "first" element. As used herein, the singular form is intended to also include the plural form, unless the context clearly states otherwise.

[0038] It will be further understood that the terms "comprises," "including," "having," and the like, when used in this specification, indicate the presence of the described features, integers, steps, operations, elements, components, or combinations thereof, but do not preclude the presence or addition of one or more other features, integers, steps, operations, elements, components, or combinations thereof. In addition, it will be understood that when an element such as a layer, film, region, or sheet is described as being "on" another element, the element may be directly on the other element, or there may be intervening elements between the two elements. Similarly, when an element such as a layer, film, region, or sheet is described as being "under" another element, the element may be directly under the other element, or there may be intervening elements between the two elements.

[0039] Unless otherwise stated, all numbers, values ​​and / or expressions used herein to indicate the amount of components, reaction conditions, polymer ingredients and mixtures will be considered to include approximate values ​​that substantially affect the various uncertainties of the measurement results that occur when obtaining these values, etc., and should therefore be understood to be modified by the term "about" in all cases. In addition, when a numerical range is disclosed in this specification, unless otherwise stated, the range is continuous and includes all values ​​from the minimum value of the range to its maximum value. In addition, when the range belongs to integer values, unless otherwise stated, all integers including the minimum value to the maximum value are included.

[0040] The anode provided in a conventional all-solid-state battery includes an anode active material such as graphite. In addition, an excess amount of solid electrolyte is added therein to ensure ionic conductivity in the anode. Therefore, the volume and weight of the anode may increase, thereby undesirably reducing the energy density of the anode.

[0041] Furthermore, graphite as an anode active material has large volume expansion and contraction due to charging and discharging of the battery, so a short circuit may occur in the anode to cause an increase in resistance, thereby undesirably shortening the life of the battery.

[0042] Meanwhile, lithium metal can be used as the anode of all-solid-state batteries, but lithium metal is expensive and has a slow reaction rate. In addition, problems such as short circuits due to the growth of dendrites and difficulty in large-scale implementation may occur.

[0043] Therefore, the present disclosure has been made in consideration of the above-mentioned conventional problems and is described in detail hereinafter.

[0044] Figure 1A An all-solid-state battery 1 according to a first embodiment of the present disclosure is shown. Figure 1A The all-solid-state battery 1 may include: an anode collector layer 10; a porous layer 20, disposed on at least one surface of the anode collector layer 10; a solid electrolyte layer 30, disposed on the porous layer 20; and a composite cathode layer 40, disposed on the solid electrolyte layer 30.

[0045] The anode current collector layer 10 may be a sheet-like substrate.

[0046] Anode current collector layer 10 may be a metal thin film including a metal selected from the group consisting of copper (Cu), nickel (Ni) and combinations thereof. Specifically, anode current collector layer 10 may be a high-density metal thin film having a porosity of less than about 1%.

[0047] The anode current collector layer 10 may have a thickness of 1 μm to 20 μm, for example 5 μm to 15 μm.

[0048] Figure 2 The porous layer 20 of the all-solid-state battery 1 is schematically shown. The porous layer 20 is a layer including pores 22 for storing lithium precipitated during charging of the all-solid-state battery 1, and the porous layer 20 may include a three-dimensional interconnected framework 21 to form the pores 22 therein.

[0049] The frame 21 is a skeleton of the porous layer 20 , and may include a metal selected from the group consisting of copper (Cu), nickel (Ni), and a combination thereof.

[0050] like Figure 2As shown, the porous layer 20 includes a first surface a in contact with the anode collector layer 10 and a second surface b in contact with the solid electrolyte layer 30. Here, the pores 22 can be distributed non-uniformly in the thickness direction within the porous layer 20, so that the pores 22a located on the first surface a are larger than the pores 22b located on the second surface b. Therefore, the non-uniform distribution of the pores 22 means that the pores 22 with different diameters are distributed in the thickness direction within the porous layer 20, which can be implemented in different ways. For example, the size of the pores 22 can be gradually increased from the second surface b to the first surface a, or the size of the pores 22b in the second surface b can be maintained at a predetermined thickness and then can be increased in a step-wise manner when reaching the first surface a.

[0051] By increasing the size of the pores 22a located on the first surface a in the manner described above, lithium precipitated during charging of the all-solid-state battery 1 can be stored in large quantities on the first surface a, particularly the anode current collector layer 10. Since lithium is in contact with the anode current collector layer 10 over a large area, lithium can be more easily converted into lithium ions during discharge of the all-solid-state battery, thereby improving charging and discharging efficiency.

[0052] The average diameter of the pores 22 is not particularly limited, for example, the average diameter of the pores 22 may be 0.01 μm to 5 μm. Here, the average diameter of the pores 22 may refer to the average diameter of the pores 22 included in the entire porous layer 20. As described above, when the pores are non-uniformly distributed in the thickness direction of the porous layer 20, the average diameter of the pores may refer to the average diameter of the pores 22 falling within a reasonable thickness range.

[0053] The porous layer 20 may have a thickness of 1 μm to 100 μm and a porosity of 10% to 99%. When the thickness and porosity of the porous layer 20 fall within the above ranges, the energy density of the all-solid-state battery may be greatly improved.

[0054] The porous layer 20 may further include at least one selected from an ionic liquid (not shown) filled in the pores 22 , a binder (not shown), and a solid electrolyte (not shown).

[0055] The ionic liquid and the solid electrolyte may be responsible for the movement of lithium ions in the porous layer 20 , and the binder may be a bonding material that connects the components of the porous layer 20 to each other.

[0056] The content of each of the ionic liquid, the solid electrolyte, and the binder is not particularly limited and may be appropriately adjusted as required.

[0057] The ionic liquid is not particularly limited, but may be selected from the group consisting of imidazolium-based, ammonium-based, pyrrolidinium-based, pyridinium-based, and phosphonium-based ionic liquids, and combinations thereof.

[0058] The solid electrolyte may be an oxide-based solid electrolyte or a sulfide-based solid electrolyte. Here, a sulfide-based solid electrolyte having high lithium ion conductivity is preferably used. The sulfide-based solid electrolyte is not particularly limited, but may include Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiI, Li 2 SP 2 S 5 -LiCl, Li 2 SP 2 S 5 -LiBr, Li 2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 -LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (where m and n are positive numbers, and Z is any one of Ge, Zn and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li x MO y(where x and y are positive numbers, and M is any one of P, Si, Ge, B, Al, Ga, and In), Li 10 G 2 S 12 The oxide-based solid electrolyte may include a garnet-type solid electrolyte, a NASICON-type solid electrolyte, a LISICON-type solid electrolyte, a perovskite-type solid electrolyte, and the like.

[0059] The binder is not particularly limited, but may include BR (butadiene rubber), NBR (nitrile butadiene rubber), HNBR (hydrogenated nitrilebutadiene rubber), PVDF (polyvinylidene difluoride), PTFE (polytetrafluoroethylene), CMC (carboxymethylcellulose), and the like.

[0060] Figure 3A A modified all-solid-state battery 1 according to the first embodiment of the present disclosure is shown. Figure 3A , the porous layer 20 may have a multi-layer structure 20 ′, 20 ′′, 20 ′′′.

[0061] When the porous layer 20 has a single layer structure, the thickness of the porous layer 20 may be uneven, and lithium may be unevenly stored in the porous layer 20. Therefore, by forming the porous layer 20 having a multilayer structure 20', 20'', 20''', the above problems may be prevented from occurring.

[0062] The porous layer 20 may be configured such that the size of the pores of the layer 20' in contact with the anode current collector layer 10 is larger than the size of the pores of the layer 20''' in contact with the solid electrolyte layer 30. When the multilayer structure of the porous layer 20 is formed as above, lithium precipitated during charging of the all-solid-state battery 1 can be stored in a large amount in the anode current collector layer 10. Since lithium is in contact with the anode current collector layer 10 over a large area, lithium can be more easily converted into lithium ions during discharge of the all-solid-state battery, thereby improving charging and discharging efficiency.

[0063] Figure 3B yes Figure 3A Magnified view of area C. Figure 3B , the seed material 50 may be provided at the interface between the layers 20', 20'', 20''' of the porous layer 20. Therefore, lithium may also be precipitated in the porous layer 20, which will be described later.

[0064] The solid electrolyte layer 30 is interposed between the porous layer 20 and the composite cathode layer 40 so that lithium ions can move between the two layers.

[0065] The solid electrolyte layer 30 may include an oxide-based solid electrolyte or a sulfide-based solid electrolyte. Here, it is preferred to use a sulfide-based solid electrolyte having high lithium ion conductivity. The sulfide-based solid electrolyte is not particularly limited, but may include Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiI, Li 2 SP 2 S 5 -LiCl, Li 2 SP 2 S 5 -LiBr, Li 2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 -LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (where m and n are positive numbers, and Z is any one of Ge, Zn and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO4 , Li 2 S-SiS 2 -Li x MO y (where x and y are positive numbers, and M is any one of P, Si, Ge, B, Al, Ga, and In), Li 10 G 2 S 12 The oxide-based solid electrolyte may include a garnet-type solid electrolyte, a NASICON-type solid electrolyte, a LISICON-type solid electrolyte, a perovskite-type solid electrolyte, and the like.

[0066] The composite cathode layer 40 may include a cathode active material layer 41 disposed on the solid electrolyte layer 30 and a cathode current collector layer 42 disposed on the cathode active material layer 41 .

[0067] The cathode active material layer 41 may include a cathode active material, a solid electrolyte, a conductive material, a binder, and the like.

[0068] The cathode active material may be an oxide active material or a sulfide active material.

[0069] The oxide active material can be LiCoO 2 、LiMnO 2 、LiNiO 2 、LiVO 2 , Li 1+x Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 Rock salt layer active materials such as LiMn 2 O 4 、Li(Ni 0.5 Mn 1.5 ) 4 Spinel active materials such as LiNiVO 4 、LiCoVO 4 Inverse spinel active materials such as LiFePO 4 、LiMnPO 4 、LiCoPO 4 、LiNiPO 4 Olivine-type active materials such as Li 2 FeSiO 4 , Li 2 MnSiO 4 Silicon-containing active materials such as LiNi 0.8 Co (0.2-x) Al x O 2A rock salt layer-type active material in which a part of transition metals in (0 < x < 0.2) is replaced by different metals, such as Li 1+x Mn 2-x-y M y O 4 (where M is at least one of Al, Mg, Co, Fe, Ni, and Zn, and 0 < x + y < 2), or a spinel-type active material in which a part of transition metals is replaced by different metals, such as Li 4 Ti 5 O 12 and lithium titanates such as this.

[0070] The sulfide active material can be copper chevrel, iron sulfide, cobalt sulfide, nickel sulfide, etc.

[0071] The solid electrolyte can be an oxide-based solid electrolyte or a sulfide-based solid electrolyte. Here, a sulfide-based solid electrolyte with high lithium ion conductivity is preferably used. The sulfide-based solid electrolyte is not particularly limited, but may include Li 2 S-P 2 S 5 、Li 2 S-P 2 S 5 -LiI、Li 2 S-P 2 S 5 -LiCl、Li 2 S-P 2 S 5 -LiBr、Li 2 S-P 2 S 5 -Li 2 O、Li 2 S-P 2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 、Li 2 S-SiS 2 -LiI、Li 2 S-SiS 2 -LiBr、Li 2 S-SiS 2 -LiCl、Li 2 S-SiS 2 -B 2 S 3 -LiI、Li 2 S-SiS 2 -P 2 S 5 -LiI、Li2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (where m and n are positive numbers, and Z is any one of Ge, Zn and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li x MO y (where x and y are positive numbers, and M is any one of P, Si, Ge, B, Al, Ga, and In), Li 10 G 2 S 12 The oxide-based solid electrolyte may include a garnet-type solid electrolyte, a NASICON-type solid electrolyte, a LISICON-type solid electrolyte, a perovskite-type solid electrolyte, etc. The solid electrolyte may be the same as or different from the solid electrolyte included in the solid electrolyte layer 30 .

[0072] The conductive material may be carbon black, conductive graphite, ethylene black, graphene, or the like.

[0073] The binder may be BR (butadiene rubber), NBR (nitrile rubber), HNBR (hydrogenated nitrile rubber), PVDF (polyvinylidene fluoride), PTFE (polytetrafluoroethylene), CMC (carboxymethyl cellulose), etc., and may be the same as or different from the binder included in the porous layer 20 .

[0074] The cathode current collector layer 42 may be aluminum foil or the like.

[0075] Figure 1B yes Figure 1A A magnified view of area A, Figure 1C yes Figure 1A Magnified view of area B. Figure 1B and Figure 1C , the all-solid-state battery 1 may be configured such that the seed material 50 is disposed at the interface between the anode current collector layer 10 and the porous layer 20 and at the interface between the porous layer 20 and the solid electrolyte layer 30 .

[0076] Reference Figure 3B When the all-solid-state battery 1 includes a porous layer 20 having a multi-layer structure, in addition to the above interfaces, the seed material 50 may also be disposed at the interfaces between the layers 20 ′, 20 ′′, 20 ′′′ of the porous layer.

[0077] The seed material 50 serves as a seed for lithium ions to move to the porous layer 20 during charging of the all-solid-state battery 1. When the all-solid-state battery 1 is charged, the lithium ions grow mainly around the seed material 50 into lithium.

[0078] The seed material 50 may include a metal element that can be alloyed with lithium. In particular, the metal element may be selected from the group consisting of lithium (Li), indium (In), gold (Au), bismuth (Bi), zinc (Zn), aluminum (Al), iron (Fe), tin (Sn), titanium (Ti) and combinations thereof.

[0079] Figure 4 is a top view showing an anode collector layer 10 according to the present disclosure and a seed material 50 formed on a surface of the anode collector layer 10. The seed material 50 may be deposited or coated on at least one surface of at least one of the anode collector layer 10 and the porous layer 20 in a predetermined shape.

[0080] The specific embodiment for forming the seed material 50 is not particularly limited. The seed material 50 may be formed on the surface of a suitable layer so that the seed material 50 may be formed on the surface of the seed material 50. Figure 1B , Figure 1C and Figure 3B The location shown in .

[0081] The process of forming the seed material 50 is not particularly limited. For example, a vapor deposition process such as physical vapor deposition (PVD), chemical vapor deposition (CVD), or a coating process such as screen printing, gravure coating, inkjet coating, etc. may be performed.

[0082] The seed material 50 may be arranged to not completely cover the above interface. That is, the seed material 50 does not form a series of layers. This is to prevent the seed material 50 from becoming a resistor in the all-solid-state battery 1. Specifically, the seed material 50 is evenly distributed on the above interface, but may be arranged to occupy 1% to 50% of the area of ​​the interface.

[0083] Figure 5 An all-solid-state battery 1 according to a second embodiment of the present disclosure is shown. Figure 5The all-solid-state battery 1 may include a three-electrode unit cell configured such that a composite cathode layer 40, a solid electrolyte layer 30, a porous layer 20, an anode current collector layer 10, a porous layer 20, a solid electrolyte layer 30, and a composite cathode layer 40 are sequentially stacked. Since the specific composition of each layer is substantially the same as that of each layer of the first embodiment described above, the specific composition of each layer will be omitted below.

[0084] Figure 6 A modified all-solid-state battery 1 according to the second embodiment of the present disclosure is shown. Figure 6 The porous layer 20 may have a multi-layer structure 20', 20'', 20'''. Since the specific composition of each layer is substantially the same as that of the first embodiment, the specific composition of each layer will be omitted below.

[0085] In order to improve the energy density per unit weight and the energy density per unit volume of an all-solid-state battery, the present disclosure provides an anode-free all-solid-state battery, which is configured such that a porous layer 20 is disposed on an anode collector layer 10, instead of using an anode including an anode active material as in a conventional all-solid-state battery.

[0086] In particular, when the present disclosure uses a porous layer 20 having a high porosity, the energy density can be greatly increased to over 400Wh / kg (800Wh / l), which is nearly twice that of a conventional lithium-ion battery.

[0087] Although specific embodiments of the present disclosure have been described with reference to the accompanying drawings, it will be understood by those skilled in the art that the present disclosure may be implemented in other specific forms without changing the technical ideas or essential features of the present disclosure. Therefore, the above embodiments should be fully understood as non-restrictive and illustrative.

Claims

1. An all-solid-state battery, comprising: an anode current collector layer; a porous layer disposed on at least one surface of the anode current collector layer and comprising a three-dimensional interconnected framework to form pores in the porous layer; A solid electrolyte layer is disposed on the porous layer; as well as a composite cathode layer disposed on the solid electrolyte layer, wherein a seed material is provided at the interface between the anode current collector layer and the porous layer and at the interface between the porous layer and the solid electrolyte layer, and The seed material is uniformly distributed at the interface and occupies 1% to 50% of the area of ​​the interface.

2. The all-solid-state battery according to claim 1, wherein: The anode current collector layer is a metal thin film including a metal selected from the group consisting of copper, nickel, and combinations thereof.

3. The all-solid-state battery according to claim 1, wherein: The anode current collector layer has a porosity of less than 1%.

4. The all-solid-state battery according to claim 1, wherein: The anode current collector layer has a thickness of 1 μm to 20 μm.

5. The all-solid-state battery according to claim 1, wherein: The frame includes a metal selected from the group consisting of copper, nickel, and combinations thereof.

6. The all-solid-state battery according to claim 1, wherein: The porous layer has a thickness of 1 μm to 100 μm.

7. The all-solid-state battery according to claim 1, wherein: The porous layer has a porosity of 10% to 99%.

8. The all-solid-state battery according to claim 1, wherein: The porous layer further includes at least one selected from an ionic liquid, a binder, and a solid electrolyte filled in the pores.

9. The all-solid-state battery according to claim 1, wherein: The porous layer has a multi-layer structure.

10. The all-solid-state battery according to claim 9, wherein: The porous layer having the multi-layer structure is configured so that the size of pores of the layer in contact with the anode current collector layer is larger than the size of pores of the layer in contact with the solid electrolyte layer.

11. The all-solid-state battery according to claim 9, wherein: The seed material is disposed at the interface between the layers of the porous layer.

12. The all-solid-state battery according to claim 1, wherein: The composite cathode layer includes a cathode active material layer disposed on the solid electrolyte layer and a cathode current collector layer disposed on the cathode active material layer.

13. The all-solid-state battery according to claim 1, wherein: The seed material is selected from the group consisting of lithium (Li), indium (In), gold (Au), bismuth (Bi), zinc (Zn), aluminum (Al), iron (Fe), tin (Sn), titanium (Ti) and combinations thereof.

14. The all-solid-state battery according to claim 1, wherein: The seed material is deposited or coated on at least one surface of at least one of the anode current collector layer and the porous layer.

15. The all-solid-state battery according to claim 1, wherein: The seed material is arranged to not completely cover the interface.

16. The all-solid-state battery according to claim 1, comprising: A three-electrode unit cell, wherein the three-electrode unit cell is configured such that the composite cathode layer, the solid electrolyte layer, the porous layer, the anode current collector layer, the porous layer, the solid electrolyte layer and the composite cathode layer are sequentially stacked.

Citation Information

Patent Citations

  • Lithium solid battery and manufacturing method thereof

    JP2019033053A

  • Battery Cell with Anode Protective Layer

    US20180358659A1